Should There Be a Recommended Daily Intake of Microbes? - Marco, Maria L; Hill, Colin; Hutkins, Robert; Slavin, Joanne; Tancredi, Daniel J; Merenstein, Daniel; Sanders, Mary Ellen (The Journal of nutrition, 2020)
ABSTRACT The collective findings from human microbiome research, randomized controlled trials on specific microbes (i.e., probiotics), and associative studies of fermented dairy consumption provide evidence for the beneficial effects of the regular consumption of safe live microbes. To test the hypothesis that the inclusion of safe, live microbes in the diet supports and improves health, we propose assessment of the types and evidentiary quality of the data available on microbe intake, including the assembly and evaluation of evidence available from dietary databases. Such an analysis would help to identify gaps in the evidence needed to test this hypothesis, which can then be used to formulate and direct initiatives focused on prospective and randomized controlled trials on live microbe consumption. Outcomes will establish whether or not the evidence exists, or can be generated, to support the establishment of dietary recommendations for live microbes.